Knowledge, attitude and practices towards COVID-19 pandemic in the community: a cross-sectional web-based survey in India - Shukla, Shruti; Deotale, Prerana (International Journal of Research in Medical Sciences, 2020)
Background: Coronavirus disease is a current new virulent disease rising its transmission and fatality with each passing day globally. People’s observance of the prevention measures is essential for controlling the spread of COVID-19, which is affected by their knowledge, attitude, and practices (KAP) towards COVID-19. The aim of this study was to assess knowledge, attitude, and practices towards COVID-19 in the community in India. Methods: Present descriptive cross-sectional study was a web-based survey carried out between 15th July and 19th July 2020 among 570 participants in Maharashtra, India. A 30-item questionnaire distributed among the public using Google forms through social media networks. Results: 97.4% participants knew contact with the infected person as a mode of transmission for COVID-19. Common symptoms of COVID-19 reported were difficulty in breathing (96.3%), fever (90.7%), cough (88.9%), sore throat (82.8%), etc. The majority of participants (>90%) had correct knowledge about preventive measures to stop the spread of COVID-19. Around 80% had a positive attitude that India will win the battle against the disease. More than 90% were practicing appropriate preventive measures while going out. Conclusions: Majority of the Indian population demonstrated good knowledge, positive attitude, and good practices regarding the COVID-19 pandemic.